Analisis Determinan Kejadian Dermatitis Akibat Kerja Pada Pemulung Di TPA Antang Kota Makassar - Maharani, Aprily Sekar; Nasruddin Syam; Ikhram Hardi (Window of Public Health Journal, 2025)
Occupational contact dermatitis is a disease caused by work due to the interaction between the skin and substances used in the work environment. These substances irritate the skin, causing damage and stimulating inflammatory reactions, so that skin irritation is the most common cause of contact dermatitis. This study aims to analyze the determinants of occupational dermatitis in scavengers of the Antang Landfill. The type of research used is Analytical Observation with a case-control design. The sample was 70 respondents. Primary data collection was obtained from interviews using questionnaires, and data processing was carried out using the SPSS program. Univariate and bivariate data analysis was carried out using the chi-square test. The results of the study were obtained based on the results of the Pearson Chi-square test, the value of ρ = 0.037, which is smaller than α (0.05), so it can be concluded that there is a relationship between work period and the occurrence of contact dermatitis in scavengers. Based on the results of the Pearson Chi-square test, the value of ρ = 0.002, which is smaller than α (0.05), so it can be concluded that there is a relationship between work history and the occurrence of contact dermatitis. Based on the results of the Pearson Chi square test, the value of ρ = 0.000 or less than 0.05) so it can be concluded that there is a relationship between the use of ganco and the incidence of contact dermatitis Based on the results of the Pearson Chi square test, the value of ρ = 0.003 or less than 0.05) so it can be concluded that there is a relationship between the use of PPE and the incidence of contact dermatitis in scavengers. This study concludes a relationship between work period, work history, use of ganco, and use of PPE with the incidence of contact dermatitis in scavengers at the Antang TPA, Makassar City.